2015
DOI: 10.4028/www.scientific.net/amm.787.270
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modelling and Simulation of Train Car Body Structure Using LS-Dyna<sup>®</sup>

Abstract: This article emphasizes on finite element modeling and simulation of train car body structure in order to ensure a crashworthy structure. Crashworthiness is a principal parameter to be considered to be taken into account in case of design of train car body structure. The present paper deals with the development of virtual prototype with energy absorption capabilities. The train car body structure with trapezoidal core has been modeled using SOLIDWORKS® software. The entire crash simulation in the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…1 At present, the material model is usually simplified when the finite element simulation of train collision is performed, and the strain rate effect of the material is generally ignored. [2][3][4][5][6] However, relevant studies on the collision behaviours of ship and automobile showed that the difference of strain rates had different influences on the structure, and the simulation results considering the strain rate effect are closer to the actual test results. [7][8][9] Therefore, it is necessary to study the dynamic constitutive relations of materials and apply these relations in the finite element simulation of train collisions, so as to improve the accuracy of the simulation.…”
Section: Introductionmentioning
confidence: 99%
“…1 At present, the material model is usually simplified when the finite element simulation of train collision is performed, and the strain rate effect of the material is generally ignored. [2][3][4][5][6] However, relevant studies on the collision behaviours of ship and automobile showed that the difference of strain rates had different influences on the structure, and the simulation results considering the strain rate effect are closer to the actual test results. [7][8][9] Therefore, it is necessary to study the dynamic constitutive relations of materials and apply these relations in the finite element simulation of train collisions, so as to improve the accuracy of the simulation.…”
Section: Introductionmentioning
confidence: 99%